Types of Phrases, Clauses and Sentences in Speech of 4 Year Old Children (Syntactic Study) - Lubna; Nurchalistiani Budiana; Prasetyo Yuli Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Language is a communication tool in the form of a sound symbol system produced by human speech organs. Language units are formed from various arrangements, including phrases, clauses, and sentences. The purpose of this study was to find out the types of phrases, clauses and sentences found in the speech of children aged 4 years with a syntactic study. The research process involved observing, listening and taking notes. The method used is descriptive qualitative. The research results obtained by researchers are in the form of 4 types of phrases, namely attributive endocentric phrases, apositive endocentric phrases, coordinating endocentric phrases, phrases, and noun phrases. While there are 2 types of clauses found, namely independent clauses and bound clauses, and the types of sentences found in this study there are 7 types of sentences.